2001
DOI: 10.1081/ada-100103712
|View full text |Cite
|
Sign up to set email alerts
|

FEDERAL PRISON RESIDENTIAL DRUG TREATMENT REDUCES SUBSTANCE USE AND ARRESTS AFTER RELEASE*

Abstract: Without controlling for selection bias, the effects of treatment would most likely have been attenuated. The results have greater generalizability than other studies of prison-based treatment. This study occurred within a multisite context of 20 programs serving both male and female inmates and operating within different security levels and different geographic regions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
75
0
1

Year Published

2004
2004
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(78 citation statements)
references
References 12 publications
2
75
0
1
Order By: Relevance
“…Ayr›ca, "Denetimli Serbestlik ve Yard›m Merkezleri ile Koruma Kurullar› Yönetmeli¤i"nin 83 üncü maddesinin on ikinci f›kras›na göre; "Tedavi tamamland›ktan sonra devam eden denetimli serbestlik tedbiri süresince, flube müdür-lü¤ü veya büroca gerekli görülmesi halinde san›k veya hükümlü, uyuflturucu veya uyar›c› madde kullan›p kullanmad›¤›n›n tespit edilmesi için sa¤l›k kurumuna sevk edilebilir. San›k veya hükümlünün Sa¤l›k Bakanl›¤›nca belirlenen sa¤l›k kurumuna sevk yaz›s› yaz›larak befl gün içinde bu kuruma baflvurmas› istenir" (3) (23), California'da 34.9±9.9 (24) olarak bildirilmektedir. Bu konuda ülkemizde yeterli çal›fl-ma bulunmad›¤›ndan karfl›laflt›rma yap›lamam›flt›r.…”
Section: Gereç Ve Yöntemunclassified
“…Ayr›ca, "Denetimli Serbestlik ve Yard›m Merkezleri ile Koruma Kurullar› Yönetmeli¤i"nin 83 üncü maddesinin on ikinci f›kras›na göre; "Tedavi tamamland›ktan sonra devam eden denetimli serbestlik tedbiri süresince, flube müdür-lü¤ü veya büroca gerekli görülmesi halinde san›k veya hükümlü, uyuflturucu veya uyar›c› madde kullan›p kullanmad›¤›n›n tespit edilmesi için sa¤l›k kurumuna sevk edilebilir. San›k veya hükümlünün Sa¤l›k Bakanl›¤›nca belirlenen sa¤l›k kurumuna sevk yaz›s› yaz›larak befl gün içinde bu kuruma baflvurmas› istenir" (3) (23), California'da 34.9±9.9 (24) olarak bildirilmektedir. Bu konuda ülkemizde yeterli çal›fl-ma bulunmad›¤›ndan karfl›laflt›rma yap›lamam›flt›r.…”
Section: Gereç Ve Yöntemunclassified
“…51,52 Although therapy is available, there are considerable contraindications, side effects, complex administration schedules, and incomplete efficacy. Finally, numerous studies argue for drug abuse treatment [53][54][55] ; currently, drug-free programs have been the norm in the U.S., and efforts to offer methadone in the correctional setting have been limited. 56,57 Improving access to methadone maintenance in corrections settings is warranted.…”
Section: Entry and During Incarceration: Prevention Of Infection Tranmentioning
confidence: 99%
“…Similarly, support has been found for the effectiveness of intensive prison treatment integrated with aftercare for those with more severe crime and drug histories and poorer education and employment backgrounds. Nevertheless, several authors have suggested that selection bias may be influencing these outcomes (Nemes, Wish, Wraight, & Messina, 2002;Pelissier et al, 1998;Pelissier et al, 2000;Pelissier et al, 2001;Wexler et al, 1999b), indicating a need for either better controlled studies or analytic strategies that take selection bias and other threats to validity into account.The modified TC prison and aftercare programs (described fully by Sacks, Sacks, & Stommel, 2003b) examined in this paper evolved from three sources. First is the body of work produced by De Leon and colleagues, which provides a full description of the TC for the addictions, the conceptual framework, program model, and treatment interventions (De Leon, 1984, 1989, 1996 De Leon & Jainchill, 1981-82, 1992De Leon, Skodol, & Rosenthal, 1973;De Leon et al, 1982).…”
mentioning
confidence: 99%